Suppose I have to factorize the following expression: This is how I do it: (because 11 + 3 = 14 & 11 * 3 = 33) But how do I factorize the following 3 expressions? Thanks, Ron
Follow Math Help Forum on Facebook and Google+
Originally Posted by rn5a Suppose I have to factorize the following expression: This is how I do it: (because 11 + 3 = 14 & 11 * 3 = 33) But how do I factorize the following 3 expressions? Thanks, Ron Q1 It's the same as x^2 - (y + 1)^2 .... Q2 4a^2 - 12a + 9 = (2a - 3)^2 .... Q3 81a^2 + 90ab + 25b^2 = (9a + 5b)^2 ....
View Tag Cloud